The Role of TLR2 in Infection and Immunity - de Oliviera Nascimento, Laura; Massari, Paola; Wetzler, Lee M. (Frontiers in Immunology, 2012)
TLR2 forms heterodimers with TLR1 and 6 and these heterodimers are recognition molecules for a panoply of pathogens, allowing for significant innate immune responses that accounts for protection from these pathogens and immune sequelae related to infection with these pathogens. These pathogens include bacteria, viruses, fungi and parasites. This review will discuss the current state of the art regarding TLR2 recognition of pathogen associated molecular patterns (PAMPS) and the relationship of the responses induced by such recognition to immune protection and pathology.